2017
DOI: 10.1186/s12199-017-0617-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 50bp Ins/Del polymorphism at promoter of the superoxide dismutase-1 on gene expression and risk of heroin dependency

Abstract: ObjectiveSuperoxide dismutase-1 (SOD1, OMIM: 147450) is one of the major antioxidant enzymes, which plays a vital role in clearance of reactive oxygen species. A genetic polymorphism of 50 bp insertion/deletion (Ins/Del) in the promoter region of the SOD1 was reported. The aims of the present study are to evaluate the influence of this polymorphism on the SOD1 mRNA levels in human peripheral blood cells and its association with risk of heroin dependency.MethodsThe present study consisted of 47 healthy students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This is a noteworthy finding, since alterations in the SOD1 promoter region sequence may cause a decrease in protein expression, as shown for other disorders. [41,42] The SOD1 protein neutralizes excess ROS in the cell, and ROS levels are increased in patients with KC. [43][44][45] Low levels of SOD1 enzyme can also result from gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This is a noteworthy finding, since alterations in the SOD1 promoter region sequence may cause a decrease in protein expression, as shown for other disorders. [41,42] The SOD1 protein neutralizes excess ROS in the cell, and ROS levels are increased in patients with KC. [43][44][45] Low levels of SOD1 enzyme can also result from gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genetic variations have been identified in the SOD1 , including a 50bp Insertion/Deletion (Ins/Del) polymorphism in the promoter region of the gene (1684 bp upstream of the ATG start codon). Studies have been reported that the Del allele reduces promoter activity of the gene (Broom et al, 2008[ 1 ]; Saify and Saadat, 2017[ 8 ]). It has been reported that although this polymorphism is not associated with the risk of bipolar disorder type 1, it is associated with age of onset of the disorder (Kordestanian and Saadat, 2017[ 2 ]).…”
Section: mentioning
confidence: 99%
“…The study was approved by the Ethics Committee of Shiraz University. Genotyping was carried out using specific primers as described previously (Saify and Saadat, 2017[ 8 ]).…”
Section: mentioning
confidence: 99%
“…A 50 bp insertion/deletion (Ins/Del) in the SOD1 promoter region has been reported ( 10 ). This is a functional polymorphism and alters gene expression with the Del allele resulting in lower SOD1 mRNA levels ( 11 ). Association between the SOD1 expression level and PE has been investigated ( 12 ).…”
Section: Introductionmentioning
confidence: 99%